Differential Diagnosis and Management of Incomplete Locked-In Syndrome after Traumatic Brain Injury - Lauren Surdyke; Jennifer Fernandez; Hannah Foster; Pamela Spigel (Case Reports in Neurological Medicine)
Locked-in syndrome (LIS) is a rare diagnosis in which patients present with quadriplegia, lower cranial nerve paralysis, and mutism. It is clinically difficult to differentiate from other similarly presenting diagnoses with no standard approach for assessing such poorly responsive patients. The purpose of this case is to highlight the clinical differential diagnosis process and outcomes of a patient with LIS during acute inpatient rehabilitation. A 32-year-old female was admitted following traumatic brain injury. She presented with quadriplegia and mutism but was awake and aroused based on eye gaze communication. The rehabilitation team was able to diagnose incomplete LIS based on knowledge of neuroanatomy and clinical reasoning. Establishing this diagnosis allowed for an individualized treatment plan that focused on communication, coping, family training, and discharge planning. The patient was ultimately able to discharge home with a single caregiver, improving her quality of life. Continued evidence highlights the benefits of intensive comprehensive therapy for those with acquired brain injury such as LIS, but access is still limited for those with a seemingly poor prognosis. Access to a multidisciplinary, specialized team provides opportunity for continued assessment and individualized treatment as the patient attains more medical stability, improving long-term management.